ALYSIS OF MICROBIAL CONTAMINATION IN RED SNAPPER (Lutjanus sp.) AS EXPORT COMMODITY IN TARAKAN CITY - Samsidar, Samsidar; Nasrudin, Abdul Rohman; Megawati, Megawati; Pamaharyani, Luchiandini Ika (Politeknik Kelautan dan Perikanan Dumai, 2024)
Red snapper (Lutjanus sp.) is one of the most popular fish species because of its delicious taste with thick and dense meat and high nutritional content such as protein, omega 3 fatty acids, vitamins, and minerals known to be very productive for heart health, brain, bones, and endurance. Red snapper (Lutjanus sp.) as a fishery product is perishable and requires good handling to maintain the quality standards of the fish. Fish quality is an important requirement in the export process based on predetermined standards to prevent biological, chemical, and physical hazards. One of the fish quality testing processes carried out is microbiological testing by looking at the Total Plate Number (ALT) of bacteria. The calculation is carried out based on the SNI 2332:2015 (How to tet microbiology-part 3: Determination of total plate count). Testing was carried out in the laboratory of the Fish Quarantine Centre, Quality Control and Safety of Fishery Products (BKIPM) in Tarakan City. The results showed that the tested red snapper samples contained 3,3 x 103 colonies/g and were still below the maximum limit of 5x105 colonies/g. Red snapper (Lutjanus sp.) in Tarakan City is considered safe and suitable for export in accordance with SNI fresh fish quality requirements in SNI 2729: 2021 and SNI 7388:2009 on the maximum limit of microbial contamination in food.